2000
DOI: 10.1021/la000900t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations of Hydrogen Storage in Carbon Nanotube Arrays

Abstract: Grand canonical ensemble Monte Carlo (GCEMC) molecular simulations of hydrogen storage at 298 and 77 K in triangular arrays of single wall carbon nanotubes (SWCNT) and in slit pores (modeling activated carbons) were performed. At 298 K the US DOE target gravimetric hydrogen storage capacity (6.5 wt %) is reached at 160 bar for optimally configured arrays of open SWCNT of wide diameter, but the equivalent volumetric capacity is ∼40% of the DOE target [695 (STP) v/v]. For slit pores at 298 K the optimal volumetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 24 publications
3
58
0
Order By: Relevance
“…In recent years, carbon materials such as carbon nanotubes (CNTs), carbon nanofibers and mechanically milled graphites have attracted attention owing to the availability of new carbon materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, most studies concerning the hydrogen storage have been carried out at high pressures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and low temperatures (80-133 K) in order to store molecular hydrogen by physisorption. It has been often reported that hydrogen storage by physisorption remains less than 4 wt% at room temperature and even high pressures [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, carbon materials such as carbon nanotubes (CNTs), carbon nanofibers and mechanically milled graphites have attracted attention owing to the availability of new carbon materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, most studies concerning the hydrogen storage have been carried out at high pressures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and low temperatures (80-133 K) in order to store molecular hydrogen by physisorption. It has been often reported that hydrogen storage by physisorption remains less than 4 wt% at room temperature and even high pressures [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies concerning the hydrogen storage have been carried out at high pressures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and low temperatures (80-133 K) in order to store molecular hydrogen by physisorption. It has been often reported that hydrogen storage by physisorption remains less than 4 wt% at room temperature and even high pressures [1,2]. Although large hydrogen uptakes by CNTs have been reported [3,4], these results have not been easily reproduced.…”
Section: Introductionmentioning
confidence: 99%
“…At 77 K and 70 bar, the simulation of hydrogen storage in triangular array of narrow nanotubes, which were widely separated ͑1.3 to 3.0 nm͒, showed that the DOE benchmark could be reached. 20 At 10 MPa and 77 K, the simulation of hydrogen adsorption capacity in a square lattice consisting of SWNTs of diameter ϳ2.2 nm and intertube spacing ϳ1.1 nm predicted a maximum gravimetric capacity of ϳ11.2 wt % and volumetric density of 60 Kg/ m 3 . 19 However, these very encouraging simulation results given by Refs.…”
Section: Introductionmentioning
confidence: 98%
“…[18][19][20][21] These simulations predicted that it is difficult to obtain the hydrogen storage capacity at room temperature to reach the target set by the U.S. Department of Energy ͑DOE͒ for automobile applications, i.e., the gravimetric storage of 6.5 wt % and the volumetric capacity of 62 Kg H 2 /m 3 . At 77 K and 70 bar, the simulation of hydrogen storage in triangular array of narrow nanotubes, which were widely separated ͑1.3 to 3.0 nm͒, showed that the DOE benchmark could be reached.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental and theoretical studies addressed the adsorption of methane on carbon-based nanoparticles. The focus remains on carbon nanotubes (CNTs) [10,[14][15][16] because of their unique properties including uniform porosity, high tensile strength and relative inertness. However, despite their promising results CNTs showed poor gas adsorption.…”
Section: Introductionmentioning
confidence: 99%